1989
DOI: 10.1182/blood.v74.5.1600.bloodjournal7451600
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against platelet membrane glycoproteins in children with acute and chronic immune thrombocytopenic purpura

Abstract: The autoimmune nature of chronic immune thrombocytopenic purpura (ITP) in adults is widely accepted. In contrast, the pathogenetic mechanism in acute and chronic ITP in children is not known. In this report, we studied 39 children with destructive thrombocytopenia, 15 patients with acute ITP and 24 patients with chronic ITP. Platelet autoantibodies to platelet glycoprotein IIb/IIIa were detected in 14 of 24 patients (58.3%) in the chronic ITP group and in four of 15 (26.7%) with acute ITP. Binding ratios (+/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 0 publications
1
30
0
2
Order By: Relevance
“…Single test sensitivities ranged from 28.1 (EIA) to 39.4% (SPRCA). Our results are consistent with those previously published by other authors [7,8,15,17,18].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Single test sensitivities ranged from 28.1 (EIA) to 39.4% (SPRCA). Our results are consistent with those previously published by other authors [7,8,15,17,18].…”
Section: Discussionsupporting
confidence: 94%
“…Antibodies against platelet membrane glycoprotein IIb/ IIIa, Ib/IX and Ia/IIa can be detected in many ITP patients [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There are conclusive data indicating that the thrombocytopenia in ITP is generated by an IgG autoantibody [8,9]. The initial observations of Harrington et al [10] established that plasma of a patient with ITP could induce thrombocytopenia in healthy volunteer subjects, and subsequent studies showed that the effecting agent inducing thrombocytopenia in patents with ITP is in the gamma globulin fraction and presumably an antibody [11].…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…At present, no clinical or laboratory parameters are available that could enable the physician to determine the prognosis or the course of the disease in an individual patient (Taub et al, 1995). Although earlier studies (Berchtold et al, 1989b) suggested that platelet gpIIb/IIIa autoantibodies were useful in differentiating between acute and chronic AITP, recent investigations could not detect significant differences in the percentage of those antibodies (Taub et al, 1995).…”
mentioning
confidence: 98%